A mowing strategy to convert red clover to annual crops in organic farming. Issue 3 (14th June 2016) - Anderson, Randy L.
Abstract: Organic producers are interested in no-till cropping systems. In this study, we found that perennial clover can be converted to corn without tillage. Conversion tactics involved fall mowing in the third year of red clover, followed by between-row mowing of weeds and volunteer red clover in corn grown during the fourth year. Corn yielded 85% of the weed-free control with mowing conversion. In contrast, weed interference in tillage-based conversion and between-row tillage reduced corn yield 53%. Weed emergence was sixfold greater in the tilled conversion. Weeds were present in the corn row with mowing, but recently developed implements could control these weeds and further support a no-till conversion method.